Campaña de lanzamiento para la marca de bebidas alcohólicas RTD "Empila" - Baldeon Rojas, Joe Anthony (2025)
This project aims to launch “Empila,” a ready-to-drink alcoholic beverage that offers an innovative blend of modern vodka and the traditional essence of chicha, creating a unique experience within the beverage market. Targeted at socioeconomic segments A and B, Empila appeals to consumers who value a healthy and practical lifestyle. The product is set to launch in October 2025 and will be distributed exclusively through indirect channels in Peru’s main cities: Lima, Arequipa, Chiclayo, Trujillo, and Cusco. The launch strategy seeks to achieve 50% brand recall and 8% market share by the end of 2025, guided by a bold yet achievable positioning and communication plan. Based on thorough market research, a graphic identity was developed to reflect the product’s essence, alongside an integrated advertising campaign. This campaign includes the creation of a compelling creative concept, a master ad piece, and a strategic media plan designed to maximize brand visibility and engagement across both digital and traditional platforms.